Mental Health and Psychosocial Functioning Over the Lifespan of German Patients Undergoing Cardiac Catheterization for Coronary Artery Disease - Schaich, Anja; Westermair, Anna L.; Munz, Matthias; Nitsche, Stefan; Willenborg, Bastian; Willenborg, Christina; Schunkert, Heribert; Erdmann, Jeanette; Schweiger, Ulrich (Frontiers in Psychiatry, 2018)
Background: Psychological problems are common in patients with coronary artery disease (CAD) and are associated with poor outcome. However, data on the prevalence of distinct mental disorders and their relevance to patients' functioning in daily life are scarce. Method: In this retrospective study, a total of 514 German patients with CAD as diagnosed by cardiac catheterization were assessed using the Mini International Neuropsychiatric Interview 5.0.0 (M.I.N.I.) and psychosocial functioning was evaluated using the Global Assessment of Functioning (GAF) scale. Results: Twenty-nine percent of the participants suffered from at least one mental disorder after the onset of their CAD (mean time since onset = 10.86 years, SD = 8.15). In comparison to the period before onset of CAD, elevated prevalence rates were found for severe depressive episodes, agoraphobia, dysthymia, panic disorder, and hypochondria. Predictors of mental disorders after the onset of CAD were female gender, younger age at onset of CAD as well as mental disorders and low GAF scores before onset. GAF scores decreased after the onset of CAD, recovered only partially, and were influenced by mental disorders before onset in women but not in men. Conclusions: Mental disorders—especially depression and agoraphobia—are frequent in patients with CAD, with women, patients with a younger age at onset of CAD and patients with any history of mental disorders especially at risk. Regardless of whether patients meet any specific diagnostic criteria, psychosocial functioning is markedly impaired after the onset of CAD, underscoring the need for specific mental health programs for this patient population. Future research, ideally using a prospective design, is necessary to confirm these findings and to further the knowledge of prevalence rates of mental disorders and of modifiable risk factors for the development of mental disorders in patients with CAD.